Analysis of The Influence of Product Quality, Price, Location, and Promotion on Consumer Purchase Interest in Convection (Case Study on Dira Ashesh) - Azzaliya Almira (Universitas Ciputra Surabaya, 2021)
The high growth of the textile industry in Indonesia and advances in the textile sector have led to the emergence of many small and medium industries in the textile sector and textile production. The large number of garment industries that have sprung up has led to increasingly fierce competition in the garment industry. The independent variables in this study are product quality (X1), Price (X2), Location (X3), and Promotion (X4). The theory used in this research is marketing management theory. The dependent variable in this study is purchase intention (Y1). This study was conducted to determine the effect of four independent variables on convection buying interest. The object of this research is the garment industry between Surabaya and Gresik. The data collection method was carried out by distributing questionnaires to 384 respondents. Research respondents came from a sample that has been determined using the purposive sampling technique. The data in this study were obtained from questionnaires distributed online, to be analyzed using the SPSS data processing application with multiple linear regression analysis equation models. The results showed that all independent variables had an effect on the dependent variable. Garment vendor Dira Ashesh is expected to improve product quality, price, location, and promotion to increase consumer buying interest.